International Law Review of the Protection of Indonesian Migrant Workers - Arvianas, Nerissa (Universitas Sebelas Maret, 2022)
Every human being has human rights that are inherent from birth and are universal, and cannot be revoked (inalienable). Human rights are inherent in all people as human beings. Indonesian Migrant Workers who work abroad also have rights that must be protected by the Indonesian government and these rights must be respected by other human beings. This study aims to determine the form of legal protection for Indonesian Migrant Workers (TKI) abroad and the obstacles the Indonesian government faces in implementing this protection law. This research is a normative research with a qualitative descriptive research type. Data collection was carried out by digging up legal reading materials which were carried out through literature study. The results of the study show that there are still obstacles in efforts to protect Indonesian Migrant Workers so that there are still many cases of crime and human rights violations experienced by Indonesian Migrant Workers.